Results far from embolization selective with adipose tissue: This work won the Hoechst Prize to the Forum of the XXVIII Uruguayan Congress of Surgery - Grillo, Angel; Pressa, Carlos; Aramburu, Ana; Acosta, Armando; Vázquez, Daniel; Purriel, Juan; Gravina, Francisco (Cirugía del Uruguay, 1978)
Until the present moment no substance had been successful in occluding vessels ·n a permanent manner. The authors, however, have conducted experiments utilizing an adipose tissue emborus which has proved useful in definitively occluding vessels. These were performed in three series, using animals. In view of the good results obtained, the method has been applied to human clinics.